African theology as liberating wisdom : celebrating life and harmony in the Evangelical Lutheran Church in Botswana - Pöntinen, Mari-Anna. (Studies in Systematic Theology, 2013)
In African Theology as Liberating Wisdom; Celebrating Life and Harmony in the Evangelical Lutheran Church in Botswana , Mari-Anna Pöntinen analyses contextual interpretations of the Christian faith in this particular church. These interpretations are based on the special wisdom tradition which embraces monistic ontology, communal ethics in botho , and the indigenous belief in God as the Source of Life, and the Root of everything that exists. The constructing theological principle in the ELCB is the downward-orientated and descending God in Christ which interprets the 'Lutheran spirit' in a liberating and empowering sense. It deals with the cultural mythos which brings Christ down into people's existence, unlike Western connotations which are considered to hinder seeing Christ and to prevent existential self-awareness.